1990
DOI: 10.1021/bi00470a004
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent spectral and kinetic properties of cytochrome c peroxidase: comparison of freshly isolated and stored enzyme

Abstract: The effect of long-term storage on the electronic absorption spectrum and the kinetic properties of cytochrome c peroxidase has been investigated. No detectable differences were observed between freshly isolated enzyme and enzyme stored below -20 degrees C, in the crystalline state, for up to 41 months. The electronic absorption spectrum and the rate of the enzyme-hydrogen peroxide reaction are essentially independent of pH in 0.1 M potassium phosphate buffers for both fresh and stored enzyme. In buffers conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 20 publications
6
89
1
Order By: Relevance
“…Thus, ascorbate peroxidase and cytochrome c peroxidase have comparable rates of reaction with hydrogen peroxide [17], but markedly different reactivities with the small reducing substrate, ascorbate.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ascorbate peroxidase and cytochrome c peroxidase have comparable rates of reaction with hydrogen peroxide [17], but markedly different reactivities with the small reducing substrate, ascorbate.…”
Section: Discussionmentioning
confidence: 99%
“…5 in nitrate containing buffers [2,32,331) or the Arg48-Leu variant (5.8 in phosphate and phosphate/ nitrate buffers [71).…”
Section: Discussionmentioning
confidence: 99%
“…Extinction coefficients and positions of the Soret maxima for the various proteins at pH 6.0 are: yCcP, 98 ± 3 mM −1 cm −1 at 408 nm; rCcP, 101 ± 3 mM −1 cm −1 at 408 nm; reduced cytochrome c(C102T), 150 ± 5 mM −1 cm −1 at 414 nm; and oxidized yeast cytochrome c(C102T), 118 ± 4 mM −1 cm −1 at 408 nm (29,39).…”
Section: Protein Concentration Determinationmentioning
confidence: 99%
“…b RZ is the purity number, the ratio of the absorbance at the Soret maximum relative to the absorbance at the maximum of the protein band near 280 nm. c Data from studies reported in references (39,44). c Data from studies reported in references (39,44).…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation